Evaluation of agreement and correlation of three occlusal indices in an assessment of orthodontic treatment need - Đorđević Jelena; Šćepan Ivana; Glišić Branislav (Vojnosanitetski Pregled)
Background/Aim. Occlusal indices are quantitative diagnostic indicators of malocclusion severity, orthodontic treatment need, complexity and outcome. The aim of this study was to determine correlations and agreement among three occlusal indices: the Index of Orthodontic Treatment Need (IOTN), the Peer Assessment Rating Index (PAR) and the Index of Complexity, Outcome and Need (ICON) in evaluating orthodontic treatment need. Methods. A total eighty study models of patients referred to the Department of Orthodontics, School of Dentistry, Belgrade, were assessed in this retrospective study. Malocclusions of various types and severity in the permanent dentition were included. Results. The Aesthetic and the Dental Health Component of IOTN determined orthodontic treatment need in 25% and 51% of the patients, respectively. PAR determined orthodontic treatment need in 59% and ICON in 53% of patients. The Aesthetic Component of IOTN and ICON had the highest correlation (Spearman's correlation coefficient 0.95, p < 0.01). Correlations between indices were 0.44 to 0.61 with statistical significance (p < 0.01). The agreement between indices, calculated using Kappa statistics, was 0.22 to 0.63. Conclusion. The most critical in malocclusion assessment was PAR. The Aesthetic Component of IOTN and ICON correlated highly (p < 0.01). Correlations between other pairs of indices were moderate (p < 0.01). The Aesthetic Component of IOTN and ICON had substantial agreement, whereas agreement between other indices was fair or moderate. ICON could replace PAR and IOTN. Application of occlusal indices enables objective evaluation of orthodontic treatment need and easier determination of the treatment priorities.